2014
DOI: 10.1186/1478-811x-12-6
|View full text |Cite
|
Sign up to set email alerts
|

A p38MAPK/MK2 signaling pathway leading to redox stress, cell death and ischemia/reperfusion injury

Abstract: BackgroundMany diseases and pathological conditions are characterized by transient or constitutive overproduction of reactive oxygen species (ROS). ROS are causal for ischemia/reperfusion (IR)-associated tissue injury (IRI), a major contributor to organ dysfunction or failure. Preventing IRI with antioxidants failed in the clinic, most likely due to the difficulty to timely and efficiently target them to the site of ROS production and action. IR is also characterized by changes in the activity of intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 59 publications
(86 reference statements)
4
74
0
1
Order By: Relevance
“…Our results suggest that hypoxia induces both the phosphorylation and oligomerization of cryab. It has been shown that cryab serine 59 phosphorylation is catalyzed by MAPKAP kinase-2 [40], effector of the p38MAPK pathway that has been previously suggested as an important mechanism triggering I/R injury through the elevation of mitochondrial ROS levels [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that hypoxia induces both the phosphorylation and oligomerization of cryab. It has been shown that cryab serine 59 phosphorylation is catalyzed by MAPKAP kinase-2 [40], effector of the p38MAPK pathway that has been previously suggested as an important mechanism triggering I/R injury through the elevation of mitochondrial ROS levels [41].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting was performed, as described previously 32, with antibodies specific for cleaved caspase 3 (9664; Cell Signaling Technology, Boston, MA). Antibody complexes were visualized using ECL (Amersham, Buckinghamshire, UK) and quantified by using ImageJ software (National Institutes of Health, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Excessive ROS production is one of the hallmarks of ischemia reperfusion injury particularly during the early phase of reperfusion, leading to oxidative stress, which further contributes to tissue damage [70]. Among potential sources of ROS, NOX1, NOX2 and NOX4 are the major ROS producing oxidases in the kidney [71][72][73][74].…”
Section: Ros-dependent Nlrp3 Inflammasome Activationmentioning
confidence: 99%